2005
DOI: 10.1029/2005gl023716
|View full text |Cite
|
Sign up to set email alerts
|

Hurricane‐forced upwelling and chlorophyll a enhancement within cold‐core cyclones in the Gulf of Mexico

Abstract: Clear skies, subsequent to Hurricane Ivan's passage across the Gulf of Mexico in September 2004, provided a unique opportunity to investigate upper ocean responses to a major hurricane. Oceanic cyclonic circulation was rapidly intensified by the hurricane's wind field (59–62 m s−1), maximizing upwelling and surface cooling (3–7°C) in two large areas along Ivan's track. Upward isothermal displacements of 50–65 m, computed from wind stress and sea surface height changes, caused rapid ventilation of thermoclines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
263
2
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 294 publications
(292 citation statements)
references
References 22 publications
21
263
2
6
Order By: Relevance
“…Hurricanes Opal (1995), Katrina (2005), and Rita (2005) are examples of Gulf of Mexico TCs that intensified rapidly over areas of thick upper ocean warm layers [Shay et al, 2000;Jaimes and Shay, 2009]. Walker et al [2005] demonstrated that the lowest sea surface temperatures (SSTs) (20-26°C) in Hurricane Ivan's cool wake occurred within two weak CCEs along its track. Ivan's wind speeds decreased rapidly in close proximity to these TC-intensified CCEs, demonstrating immediate negative feedback from cool waters.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hurricanes Opal (1995), Katrina (2005), and Rita (2005) are examples of Gulf of Mexico TCs that intensified rapidly over areas of thick upper ocean warm layers [Shay et al, 2000;Jaimes and Shay, 2009]. Walker et al [2005] demonstrated that the lowest sea surface temperatures (SSTs) (20-26°C) in Hurricane Ivan's cool wake occurred within two weak CCEs along its track. Ivan's wind speeds decreased rapidly in close proximity to these TC-intensified CCEs, demonstrating immediate negative feedback from cool waters.…”
Section: Introductionmentioning
confidence: 99%
“…Both anticyclonic warm core eddies (WCEs) and cyclonic cold core eddies (CCEs) can rapidly impact tropical cyclone (TC) intensity changes [e.g., Emanuel, 1999;Shay et al, 2000;Lin et al, 2005Lin et al, , 2009aWalker et al, 2005;Wu et al, 2007;Jaimes and Shay, 2009;Zheng et al, 2008Zheng et al, , 2010. Hurricanes Opal (1995), Katrina (2005), and Rita (2005) are examples of Gulf of Mexico TCs that intensified rapidly over areas of thick upper ocean warm layers [Shay et al, 2000;Jaimes and Shay, 2009].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…gov). Strong current jets have been reported previously in the aftermath of storm events at the Mississippi delta [Walker et al, 1996].…”
Section: Meeting Reportsmentioning
confidence: 89%
“…from page 499 east of the Mississippi delta. Walker et al [2005] showed that the hurricane wind field energized the cyclone, enhancing upwelling of its relatively shallow thermocline.…”
Section: Meeting Reportsmentioning
confidence: 99%